(3CSGSjGJ GdEOGQI GdeGdjI (B:s (3EOGQI GdSjhdI aj GdeUGQa GdJLGQjI(B-(3GdHfhc GdEdcJQhfjI(B-(3GSJNOGe GdgfOSI GdeGdjI GdESdGejI aj EOGQI GdeNGWQ HGdeUGQa GdESdGejI (B/s - (3Ndjd, hGFd QaYJ Ydjs ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdJYdje GdLGeYj ddWHGYI hGdfTQ hGdJhRjY,s, 2023)
(3jJfGhd cJGH (B((3CSGSjGJ GdEOGQI GdeGdjI(B) (3GdUGOQ Yf OGQ GdJYdje GdLGeYj ddWHGYI hGdfTQ hGdJhRjY HeUQ, hGdPj bGe HJCdjag (B((3hGFd QaYJ Ndjd(B) (3hGdPj jbY aj MhGdj (B(366) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdEOGQI GdeGdjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3EOGQI GdSjhdI aj GdeUGQa GdJLGQjI, GdHfhc GdEdcJQhfjI, GSJNOGe GdgfOSI GdeGdjI GdESdGejI aj EOGQI GdeNGWQ HGdeUGQa GdESdGejI(B.s
(3HHdjhLQGajI (B: (3UaMI (B345-353.s
Keywords: (3GdEOGQI GdeGdjIs; (3GdHfhc GdJLGQjIs -- (3eGdjIs; (3EOGQI GdSjhdI GdfbOjIs